PENINGKATAN PENGETAHUAN ANTI KORUPSI MELALUI SOSIALISASI HUKUM PADA SISWA SMKS KATOLIK SYURADIKARA - Dadi, Agustinus F Paskalino; Lay, Maria Feronika Bebhe; Peti, Maria Vianey; Gobang, Paulus Devian Asno; Reo, Petrus Kanisius Gianluigi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Corruption is one of the extraordinary crimes in Indonesia. Corruption is massive and carried out by many people from various levels of power and government. The corrupt behavior of officials has hurt the younger generation, including the students of SMKS Syuradikara. There is a feeling of uncertainty about the bleak future, which is left behind by the current generation. The fate of the younger generation is mortgaged by the greed of corrupt actors who shamelessly take something that is not their right. So what should the younger generation do? What actions should be taken so that the corruption problem no longer eats away at the life of the nation and state? This condition requires strategic and measurable efforts from various parties, such as the Komisi Pemberantasan Korupsi (KPK), law enforcement officials, state administrators, and various elements of society. The problem of corruption cannot only be addressed with repressive efforts but also through planned and measurable prevention efforts to realize an Indonesia free from corruption. The current corruption emergency requires the formation of character in the young generation of anti-corruption to be able to realize a new Indonesia that is free from corruption. Character formation can be done through cognitive debriefing about corruption and anti-corruption through socialization activities or counseling and habituation of anti-corruption character in the younger generation. If the younger generation (students) is equipped with knowledge about corruption and anti-corruption, then this knowledge can be relied on to shape the character of students. Students become aware of attitudes or actions that are categorized as corruption and begin to get used to applying anti-corruption principles and values in their attitudes and behaviors. If students from an early age understand anti-corruption values, then it will be easy for them to practice those values in their attitudes and actions. Furthermore, if they have become accustomed to living and practicing anti-corruption values and principles in their lives, then they will have legal and ethical awareness not to commit acts of corruption from an early age.